Evaluasi Program Unit Kegiatan Mahasiswa (UKM) Sepakbola Universitas Mulawarman - Eko Subastian (Jurnal Kajian dan Penelitian Umum, 2023)
The purpose of this study was to evaluate the coaching program for the Mulawarman University Football Student Activity Unit. The research method used is descriptive qualitative. The approach used in this study is the CIPP model approach. Data collection techniques through observation, interviews and documentation of administrators, coaches, athletes and parents of athletes. The results of the study concluded: 1) Context was concluded in a good category. 2) Input regarding aspects of the availability of human resources is concluded in a good category. For the aspect of the availability of facilities and infrastructure as well as funding sources, it is concluded in the medium category. 3) The process regarding aspects of the implementation of the training program, the athlete acceptance system and coordination is concluded in the good category while the aspects of the trainer acceptance system and the use of facilities and infrastructure are concluded in the moderate category. 4) The product regarding aspects of achievement and welfare is concluded in the medium category. While the organizational aspects are concluded in the less category.